ANALISIS PERBANDINGAN KINERJA KEUANGAN PT. BANK SYARIAH INDONESIA (PERSERO), Tbk SEBELUM DAN SESUDAH MERGER - Kirzia Annasia Damar Wulan (2023)
PT Bank Syariah Indonesia (Persero), Tbk (BSI) officially operates on February 1, 2021 to become one of the largest Islamic banks in Indonesia through the merger of three state-owned Islamic banks, namely PT Bank BRI Syariah (BRIS), PT Bank Syariah Mandiri (BSM), and PT Bank BNI Syariah (BNIS). The BSI merger aims to strengthen the institutionalization of the Islamic financial industry as well as to elevate Indonesia's Islamic economy in the global arena. Apart from the benefits and objectives of conducting mergers, merger activities have a significant impact on their financial performance. The writing of this scientific work aims to analyze the differences in financial performance at Bank Syariah Indonesia between before and after the merger. The method used in measuring financial performance is the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital). The data used is four years, namely two years before and two years after the merger which is sourced from the financial statements at Bank Syariah Indonesia. The results of this scientific writing show that there are significant differences in NPF, FDR, ROA and CAR indicators before and after the merger. While for the GCG indicator there is no significant difference before and after the merger. The financial condition of Bank Syariah Indonesia after the merger was better than before the merger.